The Influence of Trust, Peers, and Enjoyment on Online Donations and Continuation Intentions: An Ethical Philanthropic Approach in Islamic Economics - Utami, Cahyaning Budi; Slamet; Ashari, Teguh; Dedi Kurniawan (JOURNAL OF ISLAMIC ECONOMICS AND BUSSINES ETHICS, 2025)
Indonesia was named the most generous country from 2018 to 2024. A significant case of donation misappropriation by an agency in early July 2022 prompted varied societal reactions.  This study examines the effects of trust in online donation platforms, peer influence, and enjoyment in helping on online donation and forwarding intentions, as well as the impact of these intentions on behavioral frequency. Data were collected via a survey of 106 Indonesian citizens who had received information about online donations in the past year. The analysis employed Structural Equation Modeling-Partial Least Squares (SEM-PLS). Results indicate that trust and peer influence have a significant and positive impact on forwarding intention but do not significantly affect online donation intention. Enjoyment in helping significantly impacts both online donation and forwarding intentions. Furthermore, online donation intention significantly affects donation frequency, and forwarding intention significantly impacts forwarding frequency. This study provides managerial implications for online donation platforms, suggesting they involve donors in the distribution process to create a positive impression.